Disease burden caused by respiratory syncytial virus compared with influenza among adults: a retrospective cohort study from Eastern Finland in 2017–2018. Issue 12 (19th December 2022) - Hämäläinen, Aleksi; Savinainen, Ellamaria; Hämäläinen, Sari; Sivenius, Katariina; Kauppinen, Juha; Koivula, Irma; Patovirta, Riitta-Liisa
Abstract : Objectives: Respiratory syncytial virus (RSV) is one of the most important causes of lower respiratory tract illnesses. In this study, we examined the number and severity of RSV infections among adult patients. The underlying diseases and background information of patients with RSV were examined and compared with the patients with influenza. Design: Retrospective cohort study. Setting: Patients receiving tertiary care services in Kuopio University Hospital (KUH) district in Eastern Finland. Participants: 725 patients (152 with RSV infection and 573 with influenza) treated in KUH between November 2017 and May 2018. Primary and secondary outcome measures: Hospitalisation and mortality. Results: Compared with influenza, RSV caused a more serious disease in terms of hospitalisation (84.2% vs 66.0%, p<0.001), incidence of pneumonia (37.5% vs 23.2%, p<0.001), need for antibiotics (67.1% vs 47.3%, p<0.001) and supplemental oxygen (50.7% vs 31.2%, p<0.001). The all-cause mortality during hospitalisation and 30 days after discharge was higher among the RSV-infected patients (8.6% vs 3.5%, p=0.010). Solid malignancies (23.1% vs 5.0%, p=0.042) and chronic kidney disease (30.8% vs 5.8%, p=0.011) were more common among the RSV-infected non-survivors compared with survivors. RSV was an independent risk factor for hospitalisation (adjusted OR (aOR) 2.035; 95% CI 1.17 to 3.55) and mortality (aOR 2.288; 95% CI 1.09 to 4.81) compared with influenza. Conclusions: Among all the screened patients, those with RSV infection were older and had more underlying conditions than patients with influenza. They had increased likelihood of hospitalisation and mortality when compared with influenza. Solid malignancies and chronic kidney disease seemed to be independent risk factors for death among RSV-infected patients. During RSV and influenza epidemics, it is important to test patients with respiratory symptoms for RSV and influenza to prevent the spread of the infections among elderly and chronically ill patients.